Nationality Based Discrimination at Work : The Case of Pakistani Professionals Abroad - Aziz, Sadaf (2016)
This research aims to investigate workplace discrimination on the basis of national origin towards Pakistani professional employees abroad. The objective of this study is to highlight the unnoticed experiences of these professionals in the international community and in doing so try to understand the nature of discrimination faced by them. Taking the interpretivist approach, this research interprets the experiences of these Pakistani professionals that they have encountered in an international work setting. Twelve Pakistani professionals were interviewed working in various countries which were coded through Thematic Analysis technique. Purposive and Snowball sampling was used to select the participants for the study. Findings of the interviews helped to answer three questions; whether Pakistani professionals experience discrimination at work on the basis of their national origin, what is the nature and forms of these experiences and how did they deal with such encounters and proposed recommendations. It was found that a large number of participants denied facing discrimination at their workplace but cited incidences where they or their acquaintances were subjected to nation origin discrimination. The nature of this discrimination ranged from direct discrimination from managers and co-workers in the form of personal remarks, difference in language and demeaning behavior, company administrative policies as well as indirect or institutional discrimination such as lower remuneration, recruitment process, work visa restrictions etc. The suggested ways of dealing with such incidence of discrimination was to report it to through anti discriminatory procedures provided by the company or host country, promote networks of Pakistani professionals and adopting universal work ethics and hard work.